Sex and race differences in QRS duration - Hnatkova, Katerina; Smetana, Peter; Toman, Ondrej; Schmidt, Georg; Malik, Marek (Europace, 2016)
AIMS: The study investigated healthy subjects to study sex and race differences in QRS durations and the dependency of QRS durations on heart rates and other physiologic correlates. METHODS AND RESULTS: QRS duration and its heart rate dependency were evaluated in 420 615 electrocardiograms obtained in 523 healthy subjects including 111 females of African origin, 130 Caucasian females, 125 males of African origin, and 129 Caucasian males. The distributions of QRS/RR slopes and QRS durations at RR intervals of 1 and 0.5 s were compared between sex- and race-defined subgroups. At high heart rates, QRS duration was increased in ∼35% of all subjects, while in the others, QRS was shortened (no differences between the subgroups). At RR interval of 1 s, the QRS duration was 97.4 ± 4.6, 99.8 ± 6.0, 101.6 ± 5.3, and 104.8 ± 6.3 ms in African females, Caucasian females, African males, and Caucasian males, respectively (all differences P < 0.001). Similar statistical differences were found at an RR of 0.5 s. When accounting for the differences in lean body mass, the difference between African and Caucasian subjects was as large as the difference between females and males. Within each subgroup, the normal QRS durations differed by 15-20 and 18-25 ms at RR intervals of 1 and 0.5 s, respectively. CONCLUSION: The QRS widths are heart rate dependent and different not only between women and men but also between African and Caucasian individuals. Difference in cardiac resynchronization therapy efficacy might be expected between patients of African and Caucasian origin stratified by QRS duration.
Keywords: Young Adult; QRS/RR relationship; Male; QRS duration; mladý dospělý; sexuální faktory; Heart Conduction System; Heart Rate; běloši; Black People; černoši; Adult; dospělí; mužské pohlaví; srdeční frekvence; Normal healthy subjects; White People; lidé; převodní systém srdeční; ženské pohlaví; Humans; Sex Factors; Electrocardiography, Ambulatory; zdraví dobrovolníci pro lékařské studie; elektrokardiografie ambulantní; Female; Healthy Volunteers